Improved prognosis of Epstein-Barr virus associated childhood Hodgkin's lymphoma: study of 47 South African cases. Issue 3 (1st March 2000) - Engel, M; Essop, M F; Close, P; Hartley, P; Pallesen, G; Sinclair-Smith, C
Abstract : Aim —To study the distribution of Hodgkin's lymphoma in South African children and report the incidence of Epstein-Barr virus (EBV) as regards age, race, sex, and histological subtype; to investigate whether EBV is relevant to survival. Methods —Immunohistochemistry (IHC) and in situ hybridisation (ISH) to detect EBV were performed on 47 South African children with classical Hodgkin's lymphoma, ranging in age from 3 to 14 years and coming from different ethnic backgrounds. The correlation between the presence of the virus and clinical outcome was assessed. Results —The nodular sclerosing subtype predominated, comprising 89% of cases; the remaining 11% were of the mixed cellularity subtype. EBV was present in 68%. Full clinical data were available for 36 cases; EBV positive patients presented with less aggressive symptoms at diagnosis and had a significantly longer median survival than EBV negative patients. Conclusions —The distribution of EBV in South African childhood Hodgkin's lymphoma follows a pattern intermediate to that of industrialised and non-industrialised countries. Furthermore, our data suggest that there is an association between poor prognosis and the non-detection of EBV products in South African childhood Hodgkin's lymphoma.